An assessment of in-service teachers’ confidence and challenges of integrating technology in Tanzanian secondary schools - Loisulie, Paul; Kondo, Tabu S. (Eureka: Journal of Educational Research, 2025)
The integration of technology in education has become a global priority, with the potential to enhance teaching and learning outcomes. In Tanzania, efforts have been made to incorporate digital tools into secondary education to enhance instructional effectiveness. However, the successful adoption of technology largely depends on teachers’ confidence and their ability to overcome various challenges. This study assesses Tanzanian secondary school teachers’ confidence in using technology and the challenges they face in its integration. Using an online survey design, data were collected from teachers across different regions. Two hundred and three (N=203) in-service teachers responded to the online survey in which 80% are male. The findings indicate that prior to the intervention, 49.3% of respondents rated their ICT skills as "Average," a figure that dramatically decreased to 4% after the intervention. The findings also indicate a strong likelihood that teachers are prepared to apply Technological, Pedagogical and Content Knowledge (TPACK) principles in their teaching practices, with mean scores across various TPACK areas exceeding 4.0. Despite these positive outcomes regarding confidence to implement TPACK principles; inadequate technology infrastructure, limited technological knowledge, resistance to adopting new technologies, difficulties in aligning technological tools with their content knowledge and pedagogical strategies, and language barriers are among the challenges of applying TPACK in the classroom. By fostering an environment that supports continuous learning and adaptation among educators, Tanzania can better equip its teachers to navigate the challenges associated with effectively implementing TPACK in their classrooms.